Screening of Host Specific Lactic Acid Bacteria Active Against Escherichia coli From Massive Sample Pools With a Combination of in vitro and ex vivo Methods - Ren, Hao; Saliu, Eva-Maria; Zentek, Jürgen; Goodarzi Boroojeni, Farshad; Vahjen, Wilfried (Frontiers in Microbiology, 2019)
A novel three-step combination of in vitro and ex vivo screening was established to massively screen host derived lactic acid bacteria (LAB) from the broiler chicken intestine with inhibitory activity against Escherichia coli. In a first step, a massive sample pool consisting of 7102 broiler-derived colonies from intestinal contents were established and sub-cultured. Supernatants thereof were incubated with an E. coli model strain to screen suitable isolates with inhibitory activity. A total of 76 isolates of interest were subsequently further studied based on either pH dependent or -independent activity in the second step of the assay. Here, in-depth growth inhibition of the E. coli model strain and the potential of isolates for lactic acid production as inhibitory substance were indexed for all isolates. Resulting scatter plots of both parameters revealed five isolates with exceptional inhibitory activity that were further studied under ex vivo condition in the third step of the assay. These isolates were taxonomically classified as strains of the species Lactobacillus agilis, Lactobacillus salivarius, and Pediococcus acidilactici. Samples from the broiler chicken intestine were inoculated with the Lactobacillus isolates and the E. coli model strain. After 8 and 24 h incubation, respectively, growth of the E. coli model strain was monitored by cultivation of the E. coli strain in antibiotic supplemented medium. By their superior inhibitory activity against the E. coli model strain, one L. agilis and one L. salivarius strain were selected and characterized for further application as probiotics in broiler chicken. Additionally, their antibiotic resistance patterns and resilience under gastric stress of isolates were also characterized. The results of this study demonstrate that the novel isolation procedure was able to efficiently and rapidly isolate and identify bacterial strains from a massive sample pool with inhibitory potential against specific types of bacteria (here E. coli). The introduction of the final ex vivo selection step additionally confirmed the inhibitory activity of the strains under conditions simulating the intestinal tract of the host. Furthermore, this method revealed a general potential for the isolation of antagonistic strains that active against other pathogenic bacteria with specific biomarker.